Analysis of the Main Causes and Damages of 2010 Flood in Pakistan (A case study of Hameed Dhere & Faqir Abad District Charsadda) - Ismail Shahid; Luis Antonio Bittar Venturi (PT FORMOSA CENDEKIA GLOBAL, 2022)
This research attempts to assess the causes and damages of the 2010 flood that severely affected the Hameed Dheri and Faqeer Abad, District charssada Khyber Pakhtunkhwa (KPK) province Pakistan and suggest recommendations for overcoming future events of this nature. Pakistan is famous for its summer floods, but the 2010 flood was considered the worst of the 21st century. It broke all previous records in terms of discharge, damage and amount of rain. Flood seriously affects the agriculture sector, and physical infrastructure in the area. Flood hazard hinders the socio-economic development of the study area. Data for this study were obtained from primary and secondary sources. A total of 180 questionnaires were answered by that flood victims. However, secondary data were obtained from the Pakistan Meteorological Department, the Flood Prediction and Warning Centre, the Federal Flood Commission, the Provincial Disaster Management Authority, the Surface Waters and the Provincial Irrigation and Drainage Authority. The analysis reveals that heavy and prolonged rainfall was the main cause of the 2010 floods. In addition, the Rapid deforestation, stagnation of the river by the highway, blocking bridges by tree trunks and the subsequent collapse of temporary dams have all played their part in causing disastrous flooding in almost all rivers from KPK. This article consists of many sections. After a brief introduction of the study, section two gives a description of the study area, Section three states research methodology, Section four highlights causes of floods, Section five deals with impacts/damages of floods and section six evaluates flood hazard reduction measurements. Section seven gives findings of the study whereas section eight suggests recommendations for mitigation of flood disasters.